2020
DOI: 10.1111/nph.16365
|View full text |Cite
|
Sign up to set email alerts
|

Terminating rice innate immunity induction requires a network of antagonistic and redox‐responsive E3 ubiquitin ligases targeting a fungal sirtuin

Abstract: Summary Fungal phytopathogens can suppress plant immune mechanisms in order to colonize living host cells. Identifying all the molecular components involved is critical for elaborating a detailed systems‐level model of plant infection probing pathogen weaknesses; yet, the hierarchy of molecular events controlling fungal responses to the plant cell is not clear. Here we show how, in the blast fungus Magnaporthe oryzae, terminating rice innate immunity requires a dynamic network of redox‐responsive E3 ubiquiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 29 publications
1
33
0
Order By: Relevance
“…To our knowledge, NDPKs have not been studied in phytopathogenic fungi with specialized infection strategies. Although a subsequent study did not confirm direct interactions between Sir2 and Ndk1 (Li et al ., 2020), we had by that time already generated a NDK1 knockout strain by homologous gene replacement in the Guy11 wild‐type (WT) isolate, and our preliminary results showed that when equal numbers of spores were applied to three‐week‐old seedlings of the susceptible rice cultivar CO‐39, the Δ ndk1 ‐carrying mutant strain was non‐pathogenic compared to WT and the Δ ndk1 NDK1 complementation strain (Figure 1a). Specifically, small, uniform dark brown pinpoint flecks without visible centers formed on leaves inoculated with all of our Δ ndk1 mutant strains, but they did not produce spores, and M. oryzae could not be isolated from them, indicating they were type I lesions arising from non‐pathogenic interactions (Valent et al ., 1991).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…To our knowledge, NDPKs have not been studied in phytopathogenic fungi with specialized infection strategies. Although a subsequent study did not confirm direct interactions between Sir2 and Ndk1 (Li et al ., 2020), we had by that time already generated a NDK1 knockout strain by homologous gene replacement in the Guy11 wild‐type (WT) isolate, and our preliminary results showed that when equal numbers of spores were applied to three‐week‐old seedlings of the susceptible rice cultivar CO‐39, the Δ ndk1 ‐carrying mutant strain was non‐pathogenic compared to WT and the Δ ndk1 NDK1 complementation strain (Figure 1a). Specifically, small, uniform dark brown pinpoint flecks without visible centers formed on leaves inoculated with all of our Δ ndk1 mutant strains, but they did not produce spores, and M. oryzae could not be isolated from them, indicating they were type I lesions arising from non‐pathogenic interactions (Valent et al ., 1991).…”
Section: Resultsmentioning
confidence: 99%
“…Otherwise, downstream plant immune defenses are triggered and infection is aborted. Many disparate cellular processes related to antioxidation or the mitigation of oxidative damage—for example the superoxide dismutase system, the glutathione antioxidation system, and the fungal nitrooxidative stress response (Fernandez and Wilson, 2014; Marroquin‐Guzman et al, 2017b; Li et al ., 2020)—maintain intracellular redox homeostasis in order to facilitate plant ROS neutralization. However, it is becoming increasingly clear that these processes act collectively to tightly regulate redox balance such that perturbing one component of this network collapses the entire ROS scavenging system, resulting in planta in an unchecked host oxidative burst.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations